2018
DOI: 10.1073/pnas.1715137115
|View full text |Cite
|
Sign up to set email alerts
|

Engineering posttranslational proofreading to discriminate nonstandard amino acids

Abstract: SignificanceAccurate incorporation of nonstandard amino acids (nsAAs) is central for genetic code expansion to increase the chemical diversity of proteins. However, aminoacyl-tRNA synthetases are polyspecific and facilitate incorporation of multiple nsAAs. We investigated and repurposed a natural protein degradation pathway, the N-end rule pathway, to devise an innovative system for rapid assessment of the accuracy of nsAA incorporation. Using this tool to monitor incorporation of the nsAA biphenylalanine allo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 58 publications
2
45
0
2
Order By: Relevance
“…To evaluate the utility of our evolved recoded strains for nsAA incorporation, we isolated clonal populations from three evolved Recoded.ΔRF1-v2 strains and cotransformed them with plasmids harboring an orthogonal translation system and a reporter protein. If the orthogonal translation system is sufficiently specific for an nsAA, then nsAA incorporation is proportional to full-length reporter protein formation based on suppression of UAG codons in the gene encoding the reporter protein (50).…”
Section: Evolved Recoded Strains Show High Specificity For Nsaa Incormentioning
confidence: 99%
“…To evaluate the utility of our evolved recoded strains for nsAA incorporation, we isolated clonal populations from three evolved Recoded.ΔRF1-v2 strains and cotransformed them with plasmids harboring an orthogonal translation system and a reporter protein. If the orthogonal translation system is sufficiently specific for an nsAA, then nsAA incorporation is proportional to full-length reporter protein formation based on suppression of UAG codons in the gene encoding the reporter protein (50).…”
Section: Evolved Recoded Strains Show High Specificity For Nsaa Incormentioning
confidence: 99%
“…In Ubr1, the binding sites for the internal and N degrons are far apart, distributed along the 1,140 N-terminal residues of the 1,950-amino acid-long protein (44). By contrast, ClpS is only 106 residues long, suggesting that the canonical binding region recognizing the N degron (16,20,21,47,48) may overlap the region necessary for recognition of substrates with an N-terminal methionine and large hydrophobic amino acids at the fourth position (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the identity of the N‐terminal residue strongly influences the in vivo half‐life of proteins . Current studies have shown that ncAAs incorporated at the N terminus of proteins have varying effects on the stability of proteins in vivo . However, protein stability may be difficult to predict when more diverse molecules are used for initiation in vivo.…”
Section: Initiation With Noncanonical Amino Acids In Vivomentioning
confidence: 99%